Triclosan is associated with breast cancer via oxidative stress and relative telomere length - Cai, Xiaomin; Ning, Caibo; Fan, Linyun; Li, Yanmin; Wang, Lu; He, Heng; Dong, Tianyi; Cai, Yimin; Zhang, Ming; Lu, Zequn; Chen, Can; Shi, Ke; et al. (Frontiers in Public Health, 2023)
Triclosan (TCS), a widely prescribed broad-spectrum antibacterial agent, is an endocrine-disrupting chemical. The relationship and biological mechanisms between TCS exposure and breast cancer (BC) are disputed. We aimed to examine the correlation between urinary TCS exposure and BC risk and estimated the mediating effects of oxidative stress and relative telomere length (RTL) in the above association. This case-control study included 302 BC patients and 302 healthy individuals in Wuhan, China. We detected urinary TCS, three common oxidative stress biomarkers [8-hydroxy-2-deoxyguanosine (8-OHdG), 8-iso-prostaglandin F2α (8-isoPGF2α), 4-hydroxy-2-nonenal-mercapturic acid (HNE-MA)], and RTL in peripheral blood mononuclear cells. Significant associations were observed between log-transformed urinary concentrations of TCS, 8-OHdG, HNE-MA, 8-isoPGF2α, RTL, and BC risk, with the odds ratios (95% confidence intervals) being 1.58 (1.32 - 1.91), 3.08 (1.55 - 6.23), 3.39 (2.45 - 4.77), 3.99 (2.48 - 6.54), and 1.67 (1.35 - 2.09), respectively. Continuous TCS exposure was significantly positively correlated with RTL, HNE-MA, and 8-isoPGF2α (all P < 0.05) but not with 8-OHdG (P = 0.060) after adjusting for covariates. The mediated proportions of RTL, HNE-MA, and 8-isoPGF2α in the relationship between TCS and BC risk were 11.11%, 14.29%, and 12.84%, respectively (all P < 0.001). In conclusion, our study confirmed the deleterious effects of TCS on BC and indicated the mediating effect of oxidative stress and RTL on the correlation between TCS and BC risk.